Prevalence, Antimicrobial Susceptibility, and Distribution of Biofilm Associated Virulence Genes in Multidrug-Resistant Acinetobacter baumannii Isolated from Various Environmental Sources in Baghdad Hospitals - Obaid, Wael Adil (Iraqi Journal of Science, 2025)
It is estimated that about 20% of all hospital-acquired infections can be attributed to environmental contamination. Acinetobacter baumannii has been identified as the primary pathogen, posing a significant hazard to human health. This work aims to evaluate the frequency, and pattern of antibiotic resistance, as well as the correlation between biofilm production and the distribution of biofilm-related genotypes in multidrug-resistant A. baumannii samples isolated from a tertiary hospital environment in Baghdad, Iraq. Conventional methods, biochemical analysis, the VITEK-2 compact system, and blaoxa-51 gene amplification were employed to identify suspected isolates. The biofilm-forming capability and antibiotic susceptibility were assessed using the microtiter plate technique and disk diffusion. Isolates were then subjected to PCR technique targeting genes associated with biofilms, including ompA, csuE, bap and blaPER-1. Of the 300 samples, 21.16% were identified and verified as A. baumannii samples by the presence of the blaoxa-51 gene in all isolates. The highest distribution of environmental isolates was recorded in ventilator (21.8%) followed by pillow and bed linens (14.5%), trolleys, bedside tables (11.5%), floor (10.3%), food tables (9.2%), sink area (8%), Staff’s hand (6.7%), incubators (5.7%), doors knobs (4.6%), surgical blades (3.4%), Curtains (2.2%) and the lowest distribution was observed in chairs (1.1%). The greatest percentage of resistance was observed against Cefepime and Ciprofloxacin (100%), Ceftazidime (97.7%), and Ceftriaxone (90%). The lowest degree was reported against Sulbactam, representing 33.33%. Out of all the isolates, a significant majority (91.95%) could form biofilms. These biofilm formers were further categorized based on their level of biofilm production, with 20% classified as weak producers, 27.5% classified as moderate producers, and 52.5% classified as strong producers. The csuE gene was the most common biofilm gene in 95.4% of the samples. The ompA gene was found in 83.9% of the samples, followed by the bap gene in 80.5%. The blaPER-1 gene was the least prevalent, detected in only 10.6% of the samples. However, only biofilm-forming isolates contained blaPER-1, bap and ompA. Conversely, all biofilm-producing and non-biofilm-producing A. baumannii were found to harbor the csuE gene. In various samples obtained from hospital environments, our investigation revealed a substantial incidence of multi-drug-resistant A. baumanii. Additionally, we observed a significant presence of genes associated with biofilm formation. Therefore, it is crucial to enforce control measures to limit the dissemination and growth of A. baumannii.